PROTECTORS OF THE PLANTATION: A DETAILED STUDY ON THE USE OF BIO-PESTICIDES IN CAMBODIA - Sok, Chantrea; Vann , Kosal (Ayden Journal of Agriculture and Allied Studies, 2024)
The widespread reliance on chemical pesticides in modern agriculture, particularly in South East Asia, has bolstered crop protection but simultaneously raised pressing concerns about its detrimental impact on human health and the environment. Cambodia, in particular, has witnessed a tenfold surge in pesticide imports over the past decade, further exacerbated by illicit border imports. Given the substantial agricultural engagement of its population, this surge amplifies environmental health risks. This escalating concern has driven a growing demand to seek safer alternatives for crop protection. Bio-pesticides, offering targeted pest control with minimal residue and environmental impact, present a viable solution. While bio-pesticides have demonstrated their efficacy in Cambodian vegetable production, their adoption remains limited, largely due to farmer skepticism regarding their effectiveness and availability. In response to this challenge, this study delves into the current state of bio-pesticide use among Cambodian vegetable farmers. By scrutinizing the materials, formulation, application methods, and effectiveness of biopesticides, it seeks to provide essential insights for enhancing biopesticide management practices. Ultimately, this research aims to facilitate the wider adoption of bio-pesticides as a sustainable alternative to chemical pesticides, addressing both crop protection needs and environmental health concerns.